Turismo étnico e xamânico na Terra Indígena do Rio Gregório: um estudo sobre a construção da aldeia Yawarani - Bruno Eduardo Freitas Honorato (2020)
The main objective of this work was to identify the connections, shares and social practices associated with tourism in the Yawarani village on the indigenous land of Rio Gregório. To fulfill this objective, an ethnographic research was carried out, organized in the sense of reassembling a cosmogram that comprises the connections, deviations, compositions and translations made in the social composition of the world that appears in the interaction between the actors. The collected and constructed material met the criteria offered by Bruno Latour's Actor-Network Theory. That tourism is a social process that dynamizes cultural transformations is already known. However, I argue that tourism, in the particular ways that the indigenous people offer it, not only stimulates cultural transformation but also triggers the capacity for understanding between the different and provides the Yawanawá with the learning of ethnicity management operations that guarantee the maintenance of the indigenous people of its practices under controlled ethnic custody - which is desirable and indispensable for the construction of indigenous autonomy in an ethnodevelopment perspective - at the same time that it inserts indigenous people as political actors highly capable of communicating their demands to a new set of listeners , either on social networks or through alliances and visits to urban centers. This new world, which is born “in the relationship”, is configured as a network of connections, alliances, partnerships and accesses that are of mutual interest between indigenous and nawas; it is a world that sustains alive the political position of the indigenous people in the dialogue on the Amazon, on the use of indigenous lands and the importance of the forest in the debate on current planet conditions. This thesis discusses, above all, tourism in the indigenous land and the maintenance of indigenous modes of existence, passing through themes such as the “dissemination of indigenous culture”; cultural dynamics processes for the rescue and invention of culture; interlocution with actors from spiritualist religions, ayahuasca and New Age adherents; formalization of tourism in the indigenous land ; ayahuasca, "medicines of the forest" and its consequences; indigenization of modernity in the case of the Yawanawá; communication and translation of indigenous practices in urban environments, among other topics.